Clinical and radiographic evaluation of silver diamine fluoride versus mineral trioxide aggregate as indirect pulp capping agents in deeply carious first permanent molars a randomized clinical trial - Marwa Ahmed Ahmed Zaghloul; Manal Ahmed El Sayed; Randa Youssef Abd Al-Gawad; Ahmed Mohamed Abd El- Samad (BDJ Open)
Abstract Aim Clinical and radiographic evaluation of SDF versus MTA as indirect pulp capping agents in deeply carious first permanent molars. Methodology This study was conducted on (30) first permanent molars indicated for indirect pulp capping (IPC) randomly allocated to either SDF or MTA groups (n = 15). The molars were finally restored with glass hybrid glass ionomer restoration. Clinical assessment was conducted at 3, 6, 9 and 12 months, while radiographic assessment was performed at 6 and 12 months using predetermined criteria. Data was statistically analyzed. Results There was no statistically significant difference between both groups for all assessed clinical and radiographic parameters, including dentin bridge formation, at all follow-up periods. There was no evidence of clinical or radiographic failure in either group. Conclusions SDF showed a high success rate compared to MTA and can be considered a promising alternative IPC agent in permanent molars.